Optimization of Methods for Obtaining and Evaluating Organotypic Liver Cultures for Further Cryopreservation - Kaverinska Аnna; Prokopiuk, Volodymyr (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):290